Exploring Types of Transitivity Processes in Eighth Grade Students' Recount Text - Ervina Fadiarachmanda (Retain: Journal of Research in English Language Teaching, 2024)
Transitivity in Systemic Functional Linguistics is a way to analyze how actions, feelings, and relationships are described in clauses. Transitivity involves processes related to verbs (e.g. material, relational, mental, existential, verbal, and behavioral); participants involved in the process (e.g. actor, goal, recipient, etc.); and circumstances that are additional information (e.g. time, place, manner, etc.). This study aims to determine the most common used transitivity processes types in recount texts written by eighth grade students. This study used a qualitative research method. The researcher obtained data of 150 clauses from eighth grade students' recount texts for analysis. The data were analyzed using thematic code analysis techniques. In analyzing the data, the researcher used Halliday's SFL Transitivity Theory. This study found that most students often used material processes in their recount texts, which showed their confidence in writing declarative sentences with active verbs. The dominant use of material processes reflects their preference for stating actions or events directly and clearly. Only a few students used mental and relational processes, and even fewer used existential, verbal, and behavioral processes. Keywords: systemic functional linguistics, transitivity, recount text